Science, speculation, and the suture: comparing the 'great outdoors' in Alain Badiou, Quentin Meillassoux and Michel Houellebecq. Issue 2 (1st February 2020) - Holland, Rachel
ABSTRACT: What role should the material world play in philosophy? Or the novel for that matter? And how do scientific models relate to these questions? This article compares the speculative realist philosophy of Alain Badiou and Quentin Meillassoux with Michel Houellebecq's The Possibility of an Island (2005), arguing that despite their alliance with sciento-materialist models of the universe, these three thinkers actually reach towards a transcendent position, related to Badiou's concept of the suture. To be sutured to something is to be tied to it, and the unsutured space which these intellectuals seek is one which enables their own discipline to exceed the limitations that they perceive to be holding down others. Quentin Meillassoux uses the set theory of Georg Cantor in an attempt to enable philosophy to re-engage with the great outdoors – to access the 'in itself' in an era preoccupied with the limits of the thinking subject. Michel Houellebecq, though, takes a different approach to what he sees as the difficulty of escaping the subjective cage. For him, the novel acts as an 'unsutured' human substitute, possessing the ability to step beyond the constraints both of subjecthood and the recent cultural theory which has made subjecthood seem all-encompassing.